2018
DOI: 10.37358/rc.18.8.6512
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Patterns in Obese and Type 2 Diabetes (T2D) Patients from Romanian Black Sea Coast Region

Abstract: Gut microbiota plays a major role in the process of food absorption and low grade inflammation, two key steps in obesity and diabetes mellitus occurrence. Gut microbiota metabolites, such as short chain fatty acids (SCFA), have an important impact over the metabolic pathways like insulin signalling, incretin production and inflammation. [1-3] We aimed to study the microbiota patterns in obese and T2D patients from Black Sea Coast region, considering the ethnic mixture, environmental and geographical particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 41 publications
0
18
1
Order By: Relevance
“…In contrast with previously published studies, we observed that T2DM patients harbored a microbiota slightly enriched in butyrate-producing microorganisms, but the difference was not statistically significant. (23). In our study group, no differences were seen in case of lactobacilli abundance in the stool samples harvested from T2DM patients.…”
Section: Discussioncontrasting
confidence: 48%
“…In contrast with previously published studies, we observed that T2DM patients harbored a microbiota slightly enriched in butyrate-producing microorganisms, but the difference was not statistically significant. (23). In our study group, no differences were seen in case of lactobacilli abundance in the stool samples harvested from T2DM patients.…”
Section: Discussioncontrasting
confidence: 48%
“…Several studies showed good results when colchicine is associated with aspirin or NSAIDs in the treatment of pericarditis [28]. Idiopathic and viral pericarditis associated with pericardial effusion is often responsive to this combination of drugs [29,30]. The treatment will be targeted for the causative agent in cases where the specific etiology is known (viral or bacterial infections).…”
Section: Treatment Of Pericardial Effusionmentioning
confidence: 99%
“…Diabetes mellitus is considered an independent risk factor for colorectal cancer occurrence. [25][26][27] In our study from the total number of 763 patients diagnosed with CRC, 217 patients (28.44%) had a type of glucose metabolism disturbance. According to the type of glucose disturbance, 16 patients had type 1 diabetes, and 123 had type 2 dyabetes, the rest having a genetic predisposition and occasionally increased glucose levels in the serum.…”
Section: Resultsmentioning
confidence: 99%